LäSBarT - Språkbanken Text (University of Gothenburg, 2024)
Easy to read Swedish and texts from children's books

Lättläst svenska och barnbokstext
LäSBarT
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik